Determination of streptococcus mutans retention in acidic and neutral pH artificial saliva environment of all-ceramic materials with different surface treatment - Yeliz Hayran; Süha Kuşcu; Ali Aydın (BMC Oral Health)
Abstract Background Although surface finishing processes are effective against Streptococcus mutans biofilm, the mechanism of action of saliva with different acidity values ​​has not been studied in detail. This study aims to produce four different all-ceramic materials in a single session with CAD/CAM devices and apply two different surface finishing processes, glazing and polishing, and then determine the retention of Streptococcus mutants on the surfaces of the materials in saliva with varying levels of acidity. Methods Zirconia-reinforced lithium silicate (Vita Suprinity, Vita Zahnfabrik, Bad Saöckingen, Germany), monochromatic feldspar (Vitablocs Mark 2, Vita Zahnfabrik, Bad Saöckingen, Germany), leucite glass ceramic (IPS Empress CAD, Ivoclar Vivadent, Liechtenstein), and monolithic zirconia (Incoris TZI (Cerec) Sirona, Germany) were used in the study. The surface roughness values ​​of all samples were measured with a profilometer before the application of S. mutans biofilm. A modified Fusayama artificial saliva model was prepared to reflect the oral environment. S. mutans bacterial biofilm growth rate was determined for each group with tetrazolium dye (MTT) assay and the colony-forming unit (CFU/mL). Scanning electron microscopy was used to compare the efficacy of all-ceramic materials against bacterial biofilm. Results The surface treatment applied with polishing rubber (Ra 0.18–0.33) resulted in a slightly less rough surface than the glaze (Ra 0.32–0.35) treatment. S. mutans showed less retention in ceramic samples treated with the pH 5 saliva compared to the pH 7 ones. When this group’s percentage growth rates, colony-forming units, and scanning electron microscopy images colored with ImageJ were examined, the Glaze application reduced growth (65.02 − 91.38%) and colony formation (6.1 × 1010 – 7.8 × 1010) in all samples except for Vita Suprinity compared to the Polishing Rubber application (p < 0.05). Conclusion The pH of the salivary, the surface roughness, and the chemical content of the ceramic samples may directly affect the S. mutans biofilm formations. The Polishing Rubber of the surface treatment type should only be suggested for Vita Suprinity, whereas the Glaze of the surface treatment type should be proposed for Vita Block Mark II and InCoris TZI in an acidic salivary environment. A surface treatment method other than Glaze and Polishing Rubber should be preferred for IPS Empress CAD.